Vloga in pomen tehniškega izobraževanja v OŠ: kdo bo poučeval tehniko leta 2020? - Ploj Virtič, Mateja; Dolenc, Kosta (2017)
The Role and Importance of Technical Education in Primary Schools: Who Will Teach Techniques in 2020? We can be proud of the results of international studies (TIMSS, PISA), which rank us among the best in the world, or at least close to that, in the field of education in natural science and mathematics. However, we might ask ourselves: For how long? Based on the trajectories of the increase in the number of children per generation, the retirement trends of teachers of science, maths and technical subjects (NARMATEH) and the number of persons who graduate from university programmes for the education of teachers in these disciplines, we can predict a catastrophe - within as little as a few years, there will not be enough properly educated NARMATEH teachers to make up for the loss. This statement is supported by the fact that 1236 currently employed NARMATEH teachers will retire in 2030, 265 of whom are teachers of a primary school subject Techniques and Technology (TIT). Due to inadequate enrolment, the number of graduates that could replace them will not suffice. While university professors and staff in NARMATEH programmes may be able to ensure the high quality of our work with enrolled students, we alone can not provide incentives and material conditions, which would allow us to attract, as well as educate, future teachers.
Keywords: tehniško izobraževanje; osnovna šola; NARMATEH; Slovenija; technical education; primary school; Slovenia